Social Media as Boundary Objects: A Case of Digitalized Civic Engagement in Malaysia - Tim, Yen Ni; Pan, Shan L; Bahri, Shamshul; Fauzi, Ali (ACIS, 2014)
The emergence of social media has excited considerable interest regarding its capabilities in catalyzing enormous societal changes. Overall, the relationship between social media and civic engagement is one of the important, multifaceted areas that has received limited attention to date within the IS field. From advocacy to crime prevention, the answer to how and to what effect social media may contribute to contemporary civic engagement is still contested. By using a case study of digitalized crime fighting communities in Malaysia, we conceptualize the use of social media in catalyzing civic engagement by putting forward the notion of boundary object. Coupled with a practice lens, we offer a rich understanding of how the boundary-spanning competence of social media can be transformed in situated practice and catalyze the development of contemporary civic engagement as an instructive account that contributes to the IS literature on ICT for development.